2015
DOI: 10.1007/s11051-015-2893-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of macro-sized aluminum oxide and aluminum oxide nanoparticles on erythrocyte hemolysis: influence of cell source, temperature, and size

Abstract: Al 2 O 3 is the most abundantly produced nanomaterial and has been used in diverse fields, including the medical, military and industrial sectors. As there are concerns about the health effects of nanoparticles, it is important to understand how they interact with cells, and specifically with red blood cells. The hemolysis induced by three commercial nano-sized aluminum oxide particles (nanopowder 13 nm, nanopowder <50 nm and nanowire 2-6 nm × 200-400 nm) was compared to aluminum oxide and has been studied on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…[39][40][41] Lastly, if the coating had chemically reacted with the red blood cells, some level of degradation should have taken place. This is also true for nanoparticles, which have only been shown to be capable of inducing hemolysis, rather than strengthen red blood cells against damage.…”
Section: Hemolysismentioning
confidence: 99%
“…[39][40][41] Lastly, if the coating had chemically reacted with the red blood cells, some level of degradation should have taken place. This is also true for nanoparticles, which have only been shown to be capable of inducing hemolysis, rather than strengthen red blood cells against damage.…”
Section: Hemolysismentioning
confidence: 99%
“…16 Previous studies have reported that Al 2 O 3 NPs can show inhibitory effect on human bronchial epithelial cells and cause hemolysis of RBCs. 17,18 While the mechanisms for the cytotoxicity of different classes of nanomaterials are still under investigation, studies have shown that the direct association of NPs with cell membranes is often a critical step that precedes the subsequence biological responses. 19,20 The attachment of NPs on cell membranes can also result in damage of the membranes.…”
Section: Introductionmentioning
confidence: 99%
“…The results of a study by Vinardell P.M. et al showed that AlNPs can lyse erythrocyte as compared to macro‐sized aluminium oxide in human, rat and rabbit blood samples. The nanopowder induced a more intense haemolysis in these samples, demonstrating the risk of blood contamination by AlNPs as potent lysing nanomaterials [28]. The neurotoxicity of AlNPs has been shown in Drosophila melanogaster in which AlNPs could interrupt the neuronal rhythmic activities in the antennal lobe.…”
Section: Advantages and Limitationsmentioning
confidence: 99%